2012
DOI: 10.1111/acv.12009
|View full text |Cite
|
Sign up to set email alerts
|

Genetic population structure of the endangered fire salamander (Salamandra infraimmaculata) at the southernmost extreme of its distribution

Abstract: The negative effects of habitat fragmentation and population isolation on population viability, genetic variability and structuring are well documented, and conservation plans failing to take into account spatial population structure and connectivity can be ineffectual. Of special concern are populations at the periphery of the species range that might show reduced genetic diversity, thus affecting their adaptive potential at environmental margins. We investigated genetic variability and differentiation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 66 publications
1
20
0
Order By: Relevance
“…Peripheral populations often exhibit increased risk of inbreeding, genetic drift and natural selection (Lesica and Allendorf 1995;B€ ohme et al 2007). Blank et al (2013) investigated peripheral populations of the endangered salamander species, Salamandra infraimmaculata (Martens 1885) in Northern Israel, and found that genetic diversity was the lowest in populations at the southernmost edge of the distribution. Hoffman and Blouin (2004) found reduced levels of genetic variation in the peripheral populations of Rana pipiens (Schreber 1782) in the Pacific Northwest in the USA.…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral populations often exhibit increased risk of inbreeding, genetic drift and natural selection (Lesica and Allendorf 1995;B€ ohme et al 2007). Blank et al (2013) investigated peripheral populations of the endangered salamander species, Salamandra infraimmaculata (Martens 1885) in Northern Israel, and found that genetic diversity was the lowest in populations at the southernmost edge of the distribution. Hoffman and Blouin (2004) found reduced levels of genetic variation in the peripheral populations of Rana pipiens (Schreber 1782) in the Pacific Northwest in the USA.…”
Section: Introductionmentioning
confidence: 99%
“…All the larvae of the young cohort in each mesocosm originated from the same, randomly chosen group of larvae born to females from a different site than that of the old cohort. Previous mark-recapture work (Bar-David et al 2007) showed that adults can move between sites within that region, to which further support was lent by a population genetic survey (Blank et al 2013). Therefore, the mixing of cohorts from females that originate from different sites is a natural situation.…”
Section: Introduction Of Larvae To Mesocosmsmentioning
confidence: 92%
“…(Table 1) and four individuals previously sequenced from four of the same sites (Table S4). Maximum likelihood bootstrap values from 1,000 replications and Bayesian inference posterior probabilities are indicated, respectively, above and below the nodes when >0.5, otherwise the nodes are collapsed different species of Salamandra (Blank et al, 2013;Bani et al, 2015;Pereira, Mart ınez-Solano, & Buckley, 2016;V€ or€ os et al, 2017). The minimum number of substitutions between haplotypes is indicated along the branches.…”
Section: Sampling Peripheral Populations Of S Atramentioning
confidence: 99%